Perkembangan Dalam Kelaikan Tabrak Superstruktur Bus: Dari Kepatuhan Regulasi Hingga Perlindungan Penumpang Holistik Pada Bus Konvensional Dan Listrik - Naufal Aflah Hibatullah; Mochamad Iqbal Rokhim; Muhammad Khoirur Rijal; Slamet Raharjo (BULLET : Jurnal Multidisiplin Ilmu, 2025)
Bus accidents continue to contribute significantly to global transportation fatality statistics, particularly in developing countries where human factors and infrastructure conditions play a major role. A comprehensive synthesis of bus superstructure crashworthiness technologies is presented by tracing their evolution from basic regulatory compliance toward the challenges of future technological adaptation. While the UN ECE R66 standard has established a well-defined framework for rollover protection, a review of the literature reveals a substantial gap in frontal impact standards, leading to the adoption of truck regulations (UN ECE R29) that are often incompatible with the flat-front geometry of buses. The discussion focuses on recent findings related to validated virtual testing methodologies, innovative structural reinforcement strategies such as seat-to-pillar integration, and the critical role of occupant restraint systems in mitigating secondary injuries. Furthermore, the transition toward electric buses is identified as introducing new challenges associated with high-voltage battery protection and the brittle failure characteristics of lightweight composite materials. It is concluded that future safety paradigms must evolve beyond merely preserving occupant survival space toward a holistic approach that integrates structural optimization, occupant biomechanics, and energy storage system protection.